2016
DOI: 10.3389/fpls.2016.00109
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination of Gene Expression within Photosynthesis Pathway for Acclimation of C4 Energy Crop Miscanthus lutarioriparius

Abstract: As a promising candidate for the second-generation C4 energy crop, Miscanthus lutarioriparius has well acclimated to the water-limited and high-light Loess Plateau in China by improving photosynthesis rate and water use efficiency (WUE) compared to its native habitat along Yangtze River. Photosynthetic genes were demonstrated as one major category of the candidate genes underlying the physiological superiority. To further study how photosynthetic genes interact to improve the acclimation potential of M. lutari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…In addition, LHCI and PSI are significantly correlated with F-ATPase and C4 cycle (Xing et al 2016). Therefore, the complex consisting of LHCI, PSI, and F-ATPase plays an important role in the coordinated expression between cyclic electron transport and the CO 2 -concentrating mechanism (Xing et al 2016). In this study, several genes were found to be up-regulated in cyclic electron transport, such as PsaG, PetE, PetF, Lhca1, Lhca2, and Lhca4 (Figure 2), and the results of photosynthetic data (Figure 1(D,E)) and qPCR ( Figure 4) are in good agreement with the transcription.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, LHCI and PSI are significantly correlated with F-ATPase and C4 cycle (Xing et al 2016). Therefore, the complex consisting of LHCI, PSI, and F-ATPase plays an important role in the coordinated expression between cyclic electron transport and the CO 2 -concentrating mechanism (Xing et al 2016). In this study, several genes were found to be up-regulated in cyclic electron transport, such as PsaG, PetE, PetF, Lhca1, Lhca2, and Lhca4 (Figure 2), and the results of photosynthetic data (Figure 1(D,E)) and qPCR ( Figure 4) are in good agreement with the transcription.…”
Section: Discussionmentioning
confidence: 96%
“…The key genes, PsaG and PsaK, may be integrated after the LHCI is assembled into the PSI core complex (Ozawa et al 2010). In addition, LHCI and PSI are significantly correlated with F-ATPase and C4 cycle (Xing et al 2016). Therefore, the complex consisting of LHCI, PSI, and F-ATPase plays an important role in the coordinated expression between cyclic electron transport and the CO 2 -concentrating mechanism (Xing et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, transcriptome profiling has only been reported for genes related to water-use efficiency and high photosynthesis efficiency for M. lutarioriparius (Fan et al, 2015; Xing et al, 2016). Rhizomnousness is one of the most distinctive characteristics of M. lutarioriparius compared to the other Miscanthus species.…”
Section: Introductionmentioning
confidence: 99%
“…When M. lutarioriparius was transplanted from its native habitat to the Loess Plateau (Figure ), the low survival rate in the new environment drastically decreased genetic diversity of the transplanted population, while in the surviving plants the expression of stress‐tolerance genes showed significantly increased variation (Fan et al., ; Song et al., ; Xing et al. ; Xu et al., ). However, while these studies characterized the genetic responses of M. lutarioriparius under extremely novel conditions, we still lack information on the performance of the species in its natural populations.…”
Section: Introductionmentioning
confidence: 99%